2007
DOI: 10.1080/00365520701420750
|View full text |Cite
|
Sign up to set email alerts
|

Avenins from different cultivars of oats elicit response by coeliac peripheral lymphocytes

Abstract: There are still concerns about the suitability of including oats in a gluten-free diet. Coeliac patients consuming oats-containing food should be carefully monitored, until there is more evidence to show the safety of oats and varieties of low-toxicity oats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…The exposure of K562(S) cells to the PT digests of both oat cultivars Irina and Potenza did not result in cell agglutination, whereas some of the PT digests from oat cultivar Nave did agglutinate the K562(S) cells, though with a lower agglutination velocity than wheat flour. This result confirms the toxicity previously described for Nave oats in some in vitro models of CD inflammation [25].
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The exposure of K562(S) cells to the PT digests of both oat cultivars Irina and Potenza did not result in cell agglutination, whereas some of the PT digests from oat cultivar Nave did agglutinate the K562(S) cells, though with a lower agglutination velocity than wheat flour. This result confirms the toxicity previously described for Nave oats in some in vitro models of CD inflammation [25].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Oats include many varieties, naked and husked seeds, containing various amino acid sequences [23] and showing different immunoreactivities to anti-gliadin polyclonal antibodies [24]. We have previously reported that the prolamin avenins (the proteins corresponding to wheat gliadin) from different oat cultivars display different immunostimulatory activities on celiac lymphocytes from peripheral blood [25]. Comino et al [26] have confirmed that the immunogenicity of oats on celiac T lymphocytes differs for different cultivars and showed a direct correlation between the immunogenic ability of the oat cultivars and the concentration of the immunostimulatory gliadin peptide 33mer in their protein fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant factor in different designs is the absence of information on the oat variety used. Silano et al 24 investigated the immunogenic effect of avenins from four oat cultivars using peripheral lymphocytes from patients with CD. The results obtained in this work show that there are in fact differences in immunogenicity in the oat varieties studied.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which oats may be contaminated with gluten and whether they are safe for consumption by CD patients are issues currently being studied. [1][2][3] At any rate, a diet intentionally lacking in gluten -a gluten-free diet -has become established as the standard therapy for CD patients; adhering to a gluten-free diet has consistently been shown to induce remission in this population. 4 The exact pathogenesis of CD is not fully understood, but there appears to be an interplay between immune, genetic, and environmental factors.…”
Section: Background and Pathogenesismentioning
confidence: 99%